Comparison of Trans Canalicular Diode Laser Dacryocystorhinostomy with and Without Intubation in Patients with Acquired Nasolacrimal Duct Obstruction - Fatima Baig; Ubaid Ullah yasin; Muhammad Kamran Saeed; Khalid Baloch; Kashif Hanif; Beenish Saleem (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the outcomes of trans-canalicular diode laser dacryocystorhinostomy with and without intubation in patients with acquired nasolacrimal duct obstruction.Study Design: Quasi-Experimental studyPlace and Duration of Study: PNS Shifa Hospital Karachi, Pakistan from Jan 22 to Jan 24.Methodology: The study included 216 patients having acquired nasolacrimal duct obstruction. All the patients were randomly divided into two groups; Group-1 consisted of patients who underwent Trans Canalicular Diode Laser Dacryocystorhinostomy with intubation and Group-2 included those who underwent Trans Canalicular Diode Laser Dacryocystorhinostomy without intubation. Data analysis was done by using SPSS version 23 we employed the Chi-square test to compare qualitative variables such as gender, and laterality and an independent t-test for comparison of quantitative variables (age) between both groups.Results: A total of 216 patients were included in the study. The mean age was 45.81± 13.70 years. There was no statistically significant difference between both groups in terms of age, gender and laterality (p >0.05). The success rate was higher in Group 1 (74.1%) as compared to Group 2 (51.9%), as p-value